Characterization of the anisotropic mechanical behaviour of colonic tissues: experimental activity and constitutive formulation. Issue 5 (19th March 2014) - Carniel, E. L.; Gramigna, V.; Fontanella, C. G.; Frigo, A.; Stefanini, C.; Rubini, A.; Natali, A. N.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? The wall of the colon shows an anisotropic and non‐linear mechanical response, because of the distribution and mechanical properties of sub‐components. This study aimed to provide, by a coupled experimental and computational approach, a constitutive framework to interpret the mechanics of colonic tissues. What is the main finding and its importance? Tensile tests on tissue samples from pig colon were developed. The experimental data were processed to define proper constitutive formulations. Constitutive parameters were identified by the inverse analysis of experimental tests. The reliability of parameters was assessed by agreement between the experimental and model results and the satisfaction of material thermomechanics principles. The developed constitutive framework is capable of interpreting the general anisotropic and non‐linear mechanical behaviour of colonic tissues. The aim was to investigate the biomechanical behaviour of colonic tissues by a coupled experimental and numerical approach. The wall of the colon is composed of different tissue layers. Within each layer, different fibre families are distributed according to specific spatial orientations, which lead to a strongly anisotropic configuration. Accounting for the complex histology of the tissues, mechanical tests must be planned and designed to evaluate the behaviour of the colonic wall in different directions. Uni‐axial tensile tests were performed on tissue specimens from 15 fresh pig colons, accounting for six different loading directions (five specimens for each loading direction). The next step of the investigation was to define an appropriate constitutive framework and develop a procedure for identification of the constitutive parameters. A specific hyperelastic formulation was developed that accounted for the multilayered conformation of the colonic wall and the fibre‐reinforced configuration of the tissues. The parameters were identified by inverse analyses of the mechanical tests. The comparison of model results with experimental data, together with the evaluation of satisfaction of material thermomechanics principles, confirmed the reliability of the analysis developed. This work forms the basis for more comprehensive activities that aim to provide computational tools for the interpretation of surgical procedures that involve the gastrointestinal tract, considering the specific biomedical devices adopted.